Dynamic Matching in Cloud Manufacturing considering Matching Costs - Qi Chen; Qi Xu; Cui Wu (Complexity)
As a service-oriented business platform model, the nature of cloud manufacturing is to realise the manufacturing resources’ sharing, which will largely benefit resources supplier, resources demander, and platform operator. However, it also faces some new problems. One of the most critical issues is how to dynamically match resources of supply and demand to maximise profits of all parties while considering matching costs. This paper investigates the resources’ dynamic matching in a manufacturing supply chain that operates under a cost-sharing contract and consists of two independent and competing manufacturers and a resource-service platform. We first use differential equation to model the evolution of resource-sharing and capture the effect of matching service efforts on market demand. Next, we study the optimal matching strategies by a two-stage differential game based on the dynamic control approach. Then, we design a cost-sharing contract to coordinate and improve the supply chain’s performance. Finally, a numerical example is provided to illustrate the impact of platform transaction fees and matching costs on the feasible region of the corresponding contract.